2021
DOI: 10.52711/0974-360x.2021.01058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug related problems Encountered in Patients with Psychiatric disorders in a Secondary Care Hospital.

Abstract: Introduction: Patients with psychiatric disorders receives multiple medications associated with their comorbid conditions and mental illness increasing the risk of drug related problems leading to frequent hospitalization, healthcare expenditure and reduced quality of life. Aim/Objective: To assess and evaluate the Drug Related Problems (DRPs) encountered in patients with psychiatric disorders in a Secondary Care Hospital in Ras Al-Khaimah. Methodology: A prospective observational study was carried out for a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…DRPs were frequently identified during the study. This is consistent with the findings of other studies on cardiovascular and other hospitalized medical patients 20,25,27,29,31,35 . DRPs have been shown to be frequent in patients with cardiovascular disease 27,29,31,35 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…DRPs were frequently identified during the study. This is consistent with the findings of other studies on cardiovascular and other hospitalized medical patients 20,25,27,29,31,35 . DRPs have been shown to be frequent in patients with cardiovascular disease 27,29,31,35 .…”
Section: Discussionsupporting
confidence: 92%
“…The majority of interventions were proposed at the physician level. Our findings are similar to those of other authors 31,35,48–51 . A prospective study of DRPs in hospitalized patients at a tertiary hospital by George et al reported prescriber‐level interventions by pharmacists in 41.4% of all interventions, representing the highest percentage 48 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations